Developing 'high impact' guideline-based quality indicators for UK primary care: a multi-stage consensus process. Issue 1 (December 2015) - Rushforth, Bruno; Stokes, Tim; Andrews, Elizabeth; Willis, Thomas; McEachan, Rosemary; Faulkner, Simon; Foy, Robbie
Abstract Background Quality indicators (QIs) are an important tool for improving clinical practice and are increasingly being developed from evidence-based guideline recommendations. We aimed to identify, select and apply guideline recommendations to develop a set of QIs to measure the implementation of evidence-based practice using routinely recorded clinical data in United Kingdom (UK) primary care. Methods We reviewed existing national clinical guidelines and QIs and used a four-stage consensus development process to derive a set of 'high impact' QIs relevant to primary care based upon explicit prioritisation criteria. We then field tested the QIs using remotely extracted, anonymised patient records from 89 randomly sampled primary care practices in the Yorkshire region of England. Results Out of 2365 recommendations and QIs originally reviewed, we derived a set of 18 QIs (5 single, 13 composites – comprising 2–9 individual recommendations) for field testing. QIs predominantly addressed chronic disease management, in particular diabetes, cardiovascular and renal disease, and included both processes and outcomes of care. Field testing proved to be critical for further refinement and final selection. Conclusions We have demonstrated a rigorous and transparent methodology to develop a set of high impact, evidence-based QIs for primary care from clinical guideline recommendations. While the development process was successful in developing a limited set of QIs, it remains challenging to derive robust new QIs from clinical guidelines in the absence of established systems for routine, structured recording of clinical care.